[tex]\bf ~~~~~~~~~~~~\textit{quadratic formula} \\\\ y=\stackrel{\stackrel{a}{\downarrow }}{a}x^2\stackrel{\stackrel{b}{\downarrow }}{+b}x\stackrel{\stackrel{c}{\downarrow }}{+c} \qquad \qquad x= \cfrac{ - b \pm \sqrt { b^2 -4 a c}}{2 a} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ x=\cfrac{-8\pm\sqrt{8^2-4(1)(-10)}}{2(1)}\qquad \begin{cases} a=1\\ b=-8\\ c=-10 \end{cases}~\hfill x^2-8x-10=0[/tex]
let's bear in mind that (-8)² is really (-8)(-8), which is also (8)(8) or namely 8². Recall minus * minus = plus.